Report Card on Apprentices by Construction Trades: A Two-Year Progress Report - (:unkn) unknown (My University, 2008)
In collaboration with the Employment and Training Institute, the Milwaukee Branch of the NAACP issued a report card on minority and female participation in construction trade apprenticeship programs in the Milwaukee metro area. The report details progress made in the past two years for apprentices sponsored by 18 area joint apprenticeship committees, utilizing data from the Wisconsin Department of Workforce Development Bureau of Apprenticeship Standards. Individual report cards are provided for 519 individual companies operating in the Milwaukee area with construction trade apprentices, as of September 20, 2007. A second report assessed progress in employment by each of the joint apprenticeship committees.
Keywords: unemployment insurance; recession; job training; construction trades; apprenticeships; African Americans